2020
DOI: 10.1093/bioinformatics/btaa1067
|View full text |Cite
|
Sign up to set email alerts
|

VINYL: Variant prIoritizatioN bY survivaL analysis

Abstract: Motivation Clinical applications of genome re-sequencing technologies typically generate large amounts of data that need to be carefully annotated and interpreted to identify genetic variants potentially associated with pathological conditions. In this context, accurate and reproducible methods for the functional annotation and prioritization of genetic variants are of fundamental importance. Results In this article, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To mitigate, at least in part, some of these issues and improve the reproducibility of variant prioritization in clinical studies, our research group from the University of Milan and the CNR Institute of Biomembranes, Bioenergetics and Molecular Biotechnologies (CNR-IBIOM) have recently developed VINYL (Variant prIoritizatioN bY survivaL analysis). This novel software suite integrates an innovative method for variant prioritization, along with a highly curated collection of databases and resources for the annotation of human genetic variants [ 51 ]. The main advantage of VINYL over other existing methods is that our tool can evaluate different scoring systems and metrics for the prioritization of genetic variants and provides a fully automated procedure to derive optimal criteria for the identification of genetic variants of potential clinical relevance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate, at least in part, some of these issues and improve the reproducibility of variant prioritization in clinical studies, our research group from the University of Milan and the CNR Institute of Biomembranes, Bioenergetics and Molecular Biotechnologies (CNR-IBIOM) have recently developed VINYL (Variant prIoritizatioN bY survivaL analysis). This novel software suite integrates an innovative method for variant prioritization, along with a highly curated collection of databases and resources for the annotation of human genetic variants [ 51 ]. The main advantage of VINYL over other existing methods is that our tool can evaluate different scoring systems and metrics for the prioritization of genetic variants and provides a fully automated procedure to derive optimal criteria for the identification of genetic variants of potential clinical relevance.…”
Section: Resultsmentioning
confidence: 99%
“…The system is flexible and allows the design of custom scoring schemes based on personalized functional annotations and can be adapted/optimized to different use cases and scenarios. Notably, extensive comparisons with equivalent state of the art methods demonstrated that VINYL could detect different types of genetic variants associated with pathological conditions and achieve higher levels of sensitivity and specificity than equivalent state of the art methods [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we evaluated various classification-based feature selection algorithms on the binary classification problem of whether a patient lived longer than five years or not. The status of five-year survival was widely investigated in the conventional survival analysis studies [39,40], and a patient was generally considered as being "cancer free" if this patient lived for five years and longer [41][42][43][44]. Each feature selection algorithm was applied separately on the dataset and the subset of chosen features was used to build the classification model using one of the five classifiers with the 10-fold cross validation strategy.…”
Section: B Performance Evaluation Metricsmentioning
confidence: 99%
“…Survival time prediction is an important question for a patient with a lethal disease. This is different from the conventional survival analysis which tries to calculate the percentage of alive patients within a cohort on a time point [39,40]. Nie et al utilized the 3-dimensional convolution neural network (CNN) to extract features for an SVM model and predicted with an accuracy 89.9% whether a patient had a long or short overall survival time [88].…”
Section: Crystall a Feature Selection Algorithm To Estimate Thementioning
confidence: 99%